Diseño e implementación de un data mart de monitoreo para mejorar el control de los indicadores de gestión en la gerencia de fiscalización de hidrocarburos líquidos - osinergmin - Pastor Risco, José Fernando (2018)
The present project is to provide a solution to the problem of the need for information for decision-making by officials, in order to achieve this; a solution will be used to improve the supervision management of the institution and to meet institutional goals. During the development of the project, we evaluate the different proposed methodologies. For this purpose, the Ralph Kimball methodology will be used, which is more suited to what is to be developed by allowing the creation of Data Mart, which improves the obtaining of information by reducing the time spent in the preparation of reports by each headquarters. As a result, it was possible to implement an automated solution capable of displaying the management indicators and reports of the Favorable Technical Report and Administrative Sanctioning Procedures areas. With this project it is expected to reduce the costs of preparing reports, reduce the response time in obtaining management information, obtain a greater number of management reports, thus improving the quality of service.